Influence of woven fabric specification and yarn constitutions on the dielectric properties at ultrahigh frequency. (15th November 2017) - Jiyong, Hu; Hongyan, Jiang; Huating, Tu; Huan, Bai; Hong, Hong; Yaya, Zhang; Xudong, Yang
Abstract: With the development of off-the-shelf fabrics commonly adopted as electronic substrates, the knowledge of their electrical properties over the frequency band of interest is fundamental to correctly design the circuits. In this paper, the split post dielectric resonator is used to test the dielectric permittivity and dielectric loss tangent of woven fabrics at ultra-high frequency (UHF). The experiment uses the control variable method, and the influence of the yarn constitutions and the typical specifications of woven fabric on their dielectric properties was studied. The experimental results show that both warp yarn density and warp yarn count of these parameters have no significant effect on the permittivity and the dielectric loss tangent, and that both weft yarn density and count have nonlinear relationship with the dielectric constants. Meanwhile, fabrics with compact structure and low-crystallinity fibers have high dielectric properties. Generally, these results provide a guideline for designing the dielectric properties of woven fabric at the interested frequency.